THE RELATIONSHIP OF BABY MASSAGE WITH BABY SLEEP QUALITY AT TPMB BIDAN IKA OKTAVIA IN 2023 - Dewi Rubi Fitriani; Yayuk Sri Rahayu; Rina Dwi Anggraeni; Euis Atikah (Bajang Institute, 2024)
Baby massage is an expression of love between parents and children through skin contact. A gentle massage will relax the muscles so the baby can sleep soundly. The quality of a baby's sleep is important to support the baby's growth and development. However, unfortunately in the first year, babies often experience sleep disorders, which has a negative impact on the baby's development. Baby massage intervention is well known and widely applied, but the procedures still vary. The aim of this research is to determine the relationship between baby massage nd sleep quality in babies. The type of research used is analytical observation and cross-sectional methods. The sample used was 40 babies aged 2-12 months. The sampling method uses the total sample. The results of the study showed that 20 babies who received baby massage and had good sleep quality were 20 (100%). There is a relationship between baby massage and the sleep quality of babies aged 2-12 months, with a p value of 0.000. This research hopes that parents will pay more attention to the quality of their baby's sleep through routine baby massage, namely once every month. Through massage, the baby will feel comfortable, thus making him sleep longer and not be fussy